A Review on Algal Oil - S, Harshitha; Sarkar, Mayukh; G, Rachana; H A, Harshitha (Asian Journal of Pharmaceutical Research and Development, 2023)
Algal oil, obtained from algae, is well-known for its high concentration of omega-3 fatty acids, particularly DHA and EPA. This investigation aims to elucidate algal oil’s components and its manifold benefits for human health. This article synthesizes pharmacology aspects including dosage, administration, and side effects, as well as pharmacognostic insights like extraction types and processes, and the composition of various forms of microalgae, which may inspire novel investigation approaches. The chemical features of algal oil have been employed effectively in significant health conditions such as preterm birth, coronary heart disease, and other health concerns.